59.7=(2)(3.14)(x)

Simple and best practice solution for 59.7=(2)(3.14)(x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 59.7=(2)(3.14)(x) equation:


Simplifying
59.7 = (2)(3.14)(x)

Multiply 2 * 3.14
59.7 = 6.28x

Solving
59.7 = 6.28x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6.28x' to each side of the equation.
59.7 + -6.28x = 6.28x + -6.28x

Combine like terms: 6.28x + -6.28x = 0.00
59.7 + -6.28x = 0.00

Add '-59.7' to each side of the equation.
59.7 + -59.7 + -6.28x = 0.00 + -59.7

Combine like terms: 59.7 + -59.7 = 0.0
0.0 + -6.28x = 0.00 + -59.7
-6.28x = 0.00 + -59.7

Combine like terms: 0.00 + -59.7 = -59.7
-6.28x = -59.7

Divide each side by '-6.28'.
x = 9.506369427

Simplifying
x = 9.506369427

See similar equations:

| 8-6a=4(a-3) | | -1.333333+y+y=3 | | 3120=(26000)(0.03)(x) | | 0=12-5x+3y | | ax-r=12 | | 4(6p-8)=24p-23 | | 15r=60 | | 43z-1=4(13z-16) | | -10x+9x=-9+10 | | 1.43x(-19/37)= | | -4z-4z=3z+3+3z | | 30-10k=22-2k | | 7=12z+18-5 | | Y=yz+10 | | -8(-8x-6)=-6x-222 | | s+7(4)=16 | | 193=3+10p | | -3(-3+y)+3y=4 | | -5m=-85 | | -7(x+4)=0 | | 6n-2(3-n)=-13 | | 44+2c=7c-6 | | x/13=-7 | | 3x+3/3= | | 6(2m-1)-1(11m+6)=7 | | 7x-11=17-7x | | 60-2m=8m | | 7+14=16 | | 6x-7+3x=10+9x-7 | | 13=3x-6 | | 3-10+1-5= | | y=z+x-8/w |

Equations solver categories